Cyber-Attack: Its Definition, Regulation, and ASEAN Cooperation to Handle with it - Maskun Maskun; Irwansyah Irwansyah; Ahsan Yunus; Armelia Safira; Siti Nurhalima Lubis (Faculty of Law, Jambi University, 2021)
The development of technology brings changes in human life, and the shift of most human activities to cyberspace is now a challenge for every country in the world. Cyber-attacks are crimes that have developed rapidly with the development of information communication and technology (ICT). Due to its impact, cyber-attacks can be considered as a crime called a crime of aggression. The focus of this paper is to determine the urgency of regulating cyberattacks as a crime of aggression and to find out the extent to which the international community has made cybercrime the focus of contemporary crime research, which is referred to as a crime of aggression. This paper shows that international cooperation is needed to create an international regime that is respected and universally accepted by the international community in relation to cyber-attacks, which can also be referred to as crimes of aggression. It is because cyber-attacks in its nature are transnational crimes and need a cooperation such as the framework of ASEAN to deal with.